Tracing the History of the Arabic-Javanese Language Translation Books in Nusantara Islamic Education - Munip, Abdul (Jurnal Pendidikan Islam, 2016)
The use of Arabic script (Pegon) in the Javanese books translated from Arabic has marked a certain phase in the historical dynamics of Islamic intellectualism in Nusantara and Java in particular. By these translation activities, kitab kuning (Arabic books) are no longer enjoyed solely by the elite kyai-santri, but they can also be read by Muslims outside the walls of pesantren. The various themes of the Javaness books translated from Arabic that reach across all disciplines in Islamic teachings resulted in the rapid growing of Islamic discourse in society. Cherishing nature conveyed within the translation books generated peaceful life among Moslems. In terms of educational contexts, these book have been used in pesantren, madrasah diniyah and majelis taklim as suplementary books. Over time, most of the translated books have now metamorphosed into Indonesian edition. However, there is still numerous Arabic-Javanese language translation books occupy modest bookstalls waiting for the loyal and unpretentious readers.